Expanded data analysis and policy research for National ICT Household Survey 2019 - Jose Ramon G. Albert; Francis Mark A. Quimba; Aubrey D. Tabuga; Mary Grace Mirandilla-Santos; Maureen Ane D. Rosellon; Jana Flor V. Vizmanos; Carlos C. Cabaero; Mika S. Mu\~noz (Philippine Institute for Development Studies (PIDS), 2021)
The National ICT Household Survey (NICTHS), conducted by the Department of Information and Communications Technology (DICT) in partnership with the Philippine Statistical Research and Training Institute (PSRTI), is the first-ever household survey in the country focusing on ICT. The NICTHS is one of the strategies of DICT to jumpstart the generation of official information and communications technology (ICT) statistics critical for monitoring ICT development, particularly the expansion and diffusion of digital technologies, as well as for national development planning and policymaking. The NICTHS has a wealth of information describing households' ICT equipment and individual uses of ICT (information technology, fixed-line, and mobile Internet). This study analyzes the results of the NICTHS to help the government in developing and evaluating ICT policies and strategies, including measures to address issues, such as the digital divide, and in assessing ICT developments in the country compared to that of its peers. The study looks into ICT access and use as they pertain to living conditions (and livelihood) of households, skills of individuals (particularly in mobile telephony and the Internet), and the sharing of equipment within a household (including gender issues), that in turn, can provide clues on the potential impact of increased ICT adoption in the country on productivity, growth, jobs, and inclusion.
Keywords: 330; ICT; infrastructure; inclusion; gender